Characteristics and disclosure of local government financial statements - Haryanto Haryanto; Ofifah Dwi Novika; Warsito Kawedar; Shiddiq Nur Rahardjo (Universitas Negeri Malang, 2023)
AbstractThis study aims to examine the effect of local government characteristics on district/city Regional Government Financial Statements (LKPD) disclosures. Examination of the Characteristics of the Local Government will provide a better understanding of the disclosure of district/city Regional Government Financial Statements (LKPD). This study's independent variable consists of own-source revenue, level of dependence, total asset, capital expenditures, total population, and employee spending findings. The dependent variable is LGFR disclosure. The samples in this study are local governments with a 5-year observation period from 2016-2020. The examples were selected using the purposive sampling technique and acquired 175 pieces, which the district/city government compiled in Central Java Province and through the BPK examination process. The analytical method in this study is multiple regression analysis. The research results show that the level of dependence, total assets, capital expenditures, total population, and employee spending significantly affect the LGFR disclosure. At the same time, own-source revenue has no significant effect on the LGFR disclosure. The findings on the PAD variable align with the fact that PAD information is optional to be the focus of reporting in LKPD.AbstrakPenelitian ini bertujuan untuk menguji pengaruh karakteristik pemerintah daerah terhadap pengungkapan Laporan Keuangan Pemerintah Daerah (LKPD). Pengujian atas karakteristik Pemerintah Daerah akan memberikan pemahaman yang lebih baik atas pengungkapan Laporan Keuangan Pemerintah Daerah. Variabel independen dalam penelitian ini terdiri dari sumber kekayaan asli daerah (PAD), ketergantungan daerah, total aset, belanja modal, jumlah penduduk, dan belanja pegawai. Untuk variabel dependen yaitu pengungkapan LKPD. Penelitian ini menggunakan sampel pemerintah daerah kabupaten/kota dengan periode pengamatan tahun 2016-2020. Sampel dipilih menggunakan teknik purposive sampling dan diperoleh data sebanyak 175 sampel yang disusun pemerintah daerah kabupaten/kota di Provinsi Jawa Tengah serta sudah melalui proses pemeriksaan BPK. Metode analisis pada penelitian ini adalah analisis regresi berganda. Hasil penelitian menunjukkan bahwa total aset berpengaruh secara signifikan dan positif terhadap pengungkapan LKPD. Ketergantungan daerah, total aset, belanja modal, jumlah penduduk, dan belanja pegawai berpengaruh terhadap pengungkapan LKPD. Sedangkan, sumber kekayaan asli daerah (PAD) tidak berpengaruh signifikan terhadap pengungkapan LKPD. Hasil temuan atas variabel PAD ini sejalan dengan bahwa informasi PAD tidak menjadi fokus pelaporan dalam LKPD.